Effects of Air Pollutant Exposure on Acute Myocardial Infarction, According to Gender - Tuan,Tássia Soldi (2016)
Abstract Background: There is evidence of the effects of air pollution on hospital admissions due to cardiovascular diseases, including myocardial infarction. Objective: To estimate the association between exposure to air pollutants and hospital admissions due to myocardial infarction according to gender, between January 1st 2012 and December 31st 2013, in São Jose dos Campos-SP. Methods: An ecological time series study was carried out with daily data of admissions due to AMI, pollutants CO, O3, PM10, SO2, and NO2, according to gender. We used the Poisson regression generalized linear model to estimate the relative risks of hospital admissions with lags of 0-5 days, adjusted for temperature, humidity, seasonality and days of the week. Results: There were 1837 admissions for ischemic heart diseases, with 636 women and 1201 men. For females, the risks were significant for CO in lag 0 (RR = 1,09), lag1 (RR = 1,08) and lag 5 (RR = 1,10) and SO2 in lag 0 (RR = 1,10) and 3 (RR = 1,09). For men there was significance of the CO in, lag 3 and lag 5 (RR = 1,05). There was significance, regardless of gender, for CO at lag 1 (RR = 1,05) and lag 5 (RR = 1,07) and lag 0 for SO2 (RR = 1,06). Conclusion: The data presented show the important role of CO and SO2 in the genesis of myocardial infarction admissions, and responses to pollutant exposure are different if analyzed by gender and together - hence the importance of a stratified analyses.